A study on the use of plastic containers in the handling of wet fish / Choo Teck Keong, Vedhakumar Valliappan and Woon Kon Sung - Choo, Teck Keong; Valliappan, Vedhakumar; Woon, Kon Sung (1988)
Defining post-harvest loss is difficult, but assessing it is a near impossible task. The inherent difficulties of determining post-harvest loss is embedded in definability and a methodology that is accurate enough to show the wide spectrum of fishery losses. Whatever the level of post-harvest losses may be, economists and scientists feel more at home when it comes to attributing such losses to: factors such as improper handling, poor preservation and storage techniques, distribution and marketing problems as well as the non-utilisation of edible species.